Socio-Cultural Development's Role for Entrepreneurship and Industry to Support Green Economic Value in Java Island - Pratama, Devangga Putra Adhitya; Sakti, Norida Canda; Subroto, Waspodo Tjipto (Asian Journal of Environmental Research, 2024)
This scientific article is motivated by the description of the concept of entrepreneurship and industrial development applied to business actors in Java Island which is influenced by socio-cultural roles. The literature review in this scientific article has the following objectives: 1) to analyze the social role in the development of entrepreneurship and industry in Java Island; 2) to analyze the role of culture in the development of entrepreneurship and industry in Java Island; and 3) to analyze the concept of sociopreneur dimensions due to socio-cultural roles. This research is explained and presented with a comparative descriptive qualitative approach that focuses on the literature review scheme from the findings of 200 scientific articles discussing the socio-cultural role in the development of entrepreneurship and industry. The articles are divided into 10 articles that specifically represent the researcher's objectives to explore the socio-cultural role in Java Island. The criteria for selecting scientific articles look from the level of similarity of discussion topics, the quality of scientific articles, and the journal accreditation category from the Science and Technology Index (SINTA), Directory of Open Access Journals (DOAJ), and e-Journal of the National Library of the Republic of Indonesia. The results of the analysis show that the socio-cultural patterns that apply in the environment around the business are one of the main factors in seeing the existence of the development of the type of business that is established. So, businesses that are built from socio-cultural roles also have an impact on improving the economy in the environment around the business as feedback.